THE POTENTIAL USE OF ABO BLOOD GROUP SYSTEM IN RISK STRATIFICATION OF COVID-19 INFECTION - Jabeen, Mehir; Iqbal, Hamid; Khan, Khalid; Ahmed, Azeema; Sana, Fatima; Bashir, Saima (Infectious Diseases Journal of Pakistan, 2022)
Background: The objective behind this study was to determine the potential use of ABO blood group system in risk stratification of COVID-19 infection. Material and Methods: This cross-sectional observational study was conducted at the Department of Pathology, Combined Military Hospital (CMH), Quetta from March 2020 to February 2021. All adult patients with polymerase chain reaction (PCR) positive for Severe Acute Respiratory Syndrome Corona Virus 2 (Sars-CoV2) were evaluated for their ABO blood grouping. A comparison was made between age, severity of symptoms, place of isolation, and treatment taken with ABO blood groups by using fisher’s exact and chi-square test, a p value <0.05 was considered statistically significant. Results: A total of 218 patients who were Sars-CoV-2 PCR positive were included for final analysis. Overall mean age was 27.98±4.55 years. The most common blood group was O (n = 75, 34.4%) and least common was AB (n = 26, 11.9%). Male patients with blood group AB and O were more prevalent than other blood types, but it has insignificant association, 96.1% and 92%, respectively, p value >0.05. While, patients with blood group O were asymptomatic (60%) and patients who had blood group AB (53.8%) experienced severe symptoms, p value <0.005. Conclusions: Blood group O was the most prevalent and surprisingly least one in terms of disease related severity in patients affected by the Covid-19 infection. Keywords: COVID-19 infection, ABO blood group system, Disease susceptibility, SARS CoV-2